The study and implementation of IPv4-IPv6 multicast transition gateway - Zhang, Jian Ling (2010)
The Internet has obtained an incredible success since its birth. But some inconsiderate designs are limiting its further development to meet the demands for explosively increasing new users and devices. Besides this, some new services, such as security, multicast, mobility, QoS, etc, are also more or less influenced by current Internet due to lack of deliberate design. To address these problems, the next generation Internet Protocol, IPv6, has been proposed by IETF. However, due to IPv4 based Internet’s complicated infrastructure and IPv6’s poor backward compatibility, migration from IPv4 to IPv6 will be a long-term process that cannot be achieved over one night. To conduct a smooth transition to IPv6 and to reduce the negative influence to users and ISPs, many transition mechanisms have been proposed. Unfortunately, most proposed transition mechanisms were designed for unicast intercommunication, leaving the multicast intercommunication problem aside. Moreover, these unicast transition mechanisms are not suited for multicast transition since its one-to-many communication mode is different from unicast.